Volumetric configuration of microheometry of friction surfaces is one of the main factors of efficiency of tribosystems - Стельмах, О. У.; Сидоренко, О. Ю.; Костюнік, Р. Є. (Proceedings of National Aviation University, 2002)
It has been shown that friction surfaces with the same roughness parameter Ra determined by existing methods and devices of DSTU but with different volumetric configurations formed by the corresponding technologies with the use of the newest control methods (LSPP-03), in the process of sliding, can significantly reduce or increase frictional forces , temperature and intensity of wear of the tribosystem.